Exploring 21st-Century Skill Portrayals in an Indonesian EFL Textbook - *, Yuli Nuraeni (Journal of English Teaching and Linguistics Studies (JET Li), 2024)
This study investigates how 21st-century skills are represented in an Indonesian government-funded EFL textbook designed for first-grade junior high school students. Through content analysis, the study examines the integration of these skills within the textbook components, employing Rinekso’s (2021) framework of analysis. Results indicate comprehensive coverage of all four Cs skills (critical thinking and problem solving, communication, collaboration, creativity, and innovation), with communication skills being most prominent and creativity skills less emphasized. The representation of these skills varies across different tasks, encompassing goals, inputs, procedures, and teacher and learner roles. The findings underscore the need to expand tasks fostering creativity skills. Moreover, the study anticipates that English teachers provide practical examples of 21st-century skills in everyday contexts, fostering enthusiasm for skill development in the era of globalization.